Role Perception of Village Panchayat Pradhan in Manipur - A.Tarajit. Singh , D.K. Bose; R.K. Imotomba (Indian Journal of Extension Education, 2016)
The study was conducted in 9 C.D. Blocks in the districts of Manipur in village region. Majority of the respondents belongs to young middle age group also the respondents had ’medium’ level of socio-economic status. Dimension wise role perception results pointed that 87% of respodents’ perception of roles was high to medium in case of dimension of general role. Respondents have perceived medium level of role perception in agriculture, education, welfare and other related activities. As regards overall role perception of village Panchayat Pradhan majority (59.74%) of respondents had medium to low perception of roles. It was inferred that relationship between independent variables i.eEducation, Annual income, Mass media exposure, Leadership preference and Achievement motivation had positive and significant effect on role perception of Village Panchayat Pradhan.